The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1152/jn.00758.2010
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of A-type and Kv1- and Kv2-mediated potassium channel currents in neocortical pyramidal neurons

Abstract: Guan D, Horton LR, Armstrong WE, Foehring RC. Postnatal development of A-type and Kv1-and Kv2-mediated potassium channel currents in neocortical pyramidal neurons. J Neurophysiol 105: 2976-2988, 2011. First published March 30, 2011 doi:10.1152/jn.00758.2010.-Potassium channels regulate numerous aspects of neuronal excitability, and several voltage-gated K ϩ channel subunits have been identified in pyramidal neurons of rat neocortex. Previous studies have either considered the development of outward current as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 83 publications
(136 reference statements)
5
48
0
Order By: Relevance
“…We found that some of the GxTX-resistant current could be blocked by 1 mM TEA, but this block was not selective because 1 mM TEA also clearly partially inhibited the slowly-activating slowly-deactivating GxTX-sensitive component of current. This is consistent with a previous demonstration that the Kv2-mediated current in cortical pyramidal neurons is sensitive to low millimolar concentrations of TEA (Guan et al, 2007). Although the current remaining in GxTX-1E appeared heterogenous and varied in its kinetics from cell to cell, the GxTX-sensitive component was highly consistent in its voltage dependence and kinetics from cell to cell.…”
Section: Gxtx-1e Inhibits Most Delayed-rectifier Potassium Current Insupporting
confidence: 92%
See 4 more Smart Citations
“…We found that some of the GxTX-resistant current could be blocked by 1 mM TEA, but this block was not selective because 1 mM TEA also clearly partially inhibited the slowly-activating slowly-deactivating GxTX-sensitive component of current. This is consistent with a previous demonstration that the Kv2-mediated current in cortical pyramidal neurons is sensitive to low millimolar concentrations of TEA (Guan et al, 2007). Although the current remaining in GxTX-1E appeared heterogenous and varied in its kinetics from cell to cell, the GxTX-sensitive component was highly consistent in its voltage dependence and kinetics from cell to cell.…”
Section: Gxtx-1e Inhibits Most Delayed-rectifier Potassium Current Insupporting
confidence: 92%
“…The voltage dependence of the collected data was described fairly well by a simple Boltzmann curve constructed from the averaged midpoints and slope factors of the individual cells, with a midpoint of Ϫ11.2 Ϯ 1.3 mV and slope factor of 10.4 Ϯ 0.5 mV (n ϭ 20). This voltage dependence is generally similar to that of Kv2 current in neocortical pyramidal neurons defined by stromatoxin block (midpoint Ϫ3 mV, slope factor 10.5 mV; Guan et al, 2007) and a component of current in globus pallidus neurons with slow deactivation proposed to be Kv2 mediated (midpoint Ϫ18 mV, slope factor 7 mV; Baranauskas et al, 1999). Figure 8 shows the kinetics of the GxTX-sensitive current in CA1 pyramidal neurons.…”
Section: Gxtx-1e Inhibits Most Delayed-rectifier Potassium Current Inmentioning
confidence: 52%
See 3 more Smart Citations